Analysis of Current, Filler Metal, and Groove on Tensile Strength and Hardness of Dissimilar Welding Using Gas Tungsten Arc Welding (GTAW) - Eriek Wahyu Restu Widodo; Vuri Ayu Setyowati; Suheni Suheni; Amang Kuswanto; M. Wiji Santoso (Jurnal Teknik Mesin (JTM), 2018)
Dissimilar welding commonly used on many industries, for example power plan field. This paper presents the investigations carried out to study the influence of current, filler metal, and groove on 304 Stainless Steel to AISI 1040 Carbon Steel dissimilar joints. Gas Tungsten Arch Welding (GTAW) was conducted to join the both of base metals. 100 and 120 Ampere of current were conducted on this research, V and double-V groove with 70o of the angle as well. The maximum hardness was obtained 623.2 HVN of ER 70S-6 filler metal with 120 A of current and V groove. While the maximum tensile strength was obtained from the joint using ER 308L with 100 A of current and V-groove of 673.74 MPa. The HAZ region was obtained from the joint using double-V groove was wider than HAZ region of joint using V-groove according the macrostructure image of the joints.